PENGARUH JARAK TANAM DAN MULSA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT (Lycopersicon esculentum Mill) PADA MUSIM PENGHUJAN - Suprianto, Amelia Nur; Kurniastuti, Tri (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2017)
This research aims 1) To determine the effect of interaction of different plant spacing and the provision of mulch to growth and yield of tomato plants. 2) To know the different spacing affect the growth and yield of tomato plants. 3) To know the use of mulch type effect on growth and yield of tomato plants. This research was conducted by using Randomized Block Design in Factorial (RAK) with 2 factors, first factor is plant spacing (J) consisting of 3 levels ie 40x30 cm (J1), 40x50 cm (J2), 40x70 cm (J3) . The second factor is mulch (M) consisting of 3 levels ie: without mulch (M0 / control), straw mulch (M1), plastic mulch (M2). The variables observed were plant height, number of branches, number of bunches, number of fruit, and fruit weight. Data were analyzed by using variance analysis (Anova), 5% level. The results showed that: There was no interaction between plant spacing and mulch on growth and yield of tomato plants. Treatment spacing 40x50 (J2) effect on the number of bunches of 35 HST, the weight of the first harvest fruit and total fruit weight. The use of straw mulch type (M1) has an effect on plant height, number of branches, number of 35 HST bunches, and total fruit weight.